Engineered human pluripotent stem cell derived cardiomyocyte platforms to detect cardiovascular safety liabilities - Firth, Karl (2017)
The development and screening of new chemical entities is often a lengthy and costly process, which relies heavily on the use of animal models for measuring pre-clinical drug safety liabilities. It has been estimated that it now costs pharmaceutical companies in excess of $1 billion and takes typically between 10 - 15 years for the finished product to reach the market, with cardiovascular safety liabilities being one of the leading causes of drug attrition. The ability to convert human induced pluripotent stem cells into cardiomyocytes (hiPSC-CMs) could provide an alternative approach for drug testing. As part of a consortium led by the University of Nottingham and aligned with the CRACK-IT InPulse challenge, this work sought to develop a toxicity screening platform for use in cardiovascular safety liability testing. As part of this work, polymer substrates with a tuneable elastic modulus (in the range of 30kPa – 1780kPa) were developed, as well as the use of customisable surface micro-patterning to induce alignment of the cells. The screening platform was then optimised for use with the CellOPTIQ system, which is an optical medium-high throughput screening platform capable of detecting key cardiac readouts relating to contractility, electrophysiology and intracellular calcium handling. Functional improvements to CM maturation was achieved through the use of a novel compound Canertinib, which resulted in the recording of a positive staircase effect for contraction amplitude. It was ultimately shown that the screening platform developed as part of this work was capable of detecting cardiotoxicity. As evident by the recording of a positive inotropic response to Digoxin and a negative inotropic response to Nifedipine for contraction amplitude (156 ± 12.2% & 15.4 ± 1.3%, respectively) relative to the baseline. Future work will involve further validation of the platform by screening a range of positive, negative and neutral inotropic compounds, as well as continued work on improving the functional maturation of the cells.